Frasem In The Tontemboan Language Of The Makela’i And Matana’i Dialects - Mandolang, Nova Olvie; Garryn Ch. Ranuntu; Rosalina R. Rambing (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Language is an arbitrary system of sound symbols used by members of social groups to cooperate, communicate and identify themselves. Every country has its own language, which can be used as the country's national identity. Indonesia , has a variety of regional languages that must be preserved, in addition to the Indonesian language, because the diversity of regional languages in Indonesia is a distinctive feature of the Indonesian nation. The Tontemboan language belongs to the language group in the northern part of Indonesia and is a sub-group of the Philippine language family. In essence, the Tontemboan language has two dialectical variations namely Makela'i and Matana'i. It takes effort and hard work to reconstruct documents concerning the Tontemboan language, more specifically regarding frasem in the Tontemboan language with two dialectal variations, namely Makela'i and Matana'i. Frasem patterns in the Tontemboan language are important to study, because frasem as a series of words can be found in every expression, proverb, saying, idiom, collocation, and compound word, all of which can be an interesting picture to master. The method used in this research is descriptive qualitative by referring to Bogdan and Taylor's view of qualitative research. According to Bogdan and Taylor, qualitative research is a research procedure that is able to produce descriptive data in the form of speech, writing, and behavior of the people observed. The novelty result of this research is the description of patterns and categories of phrases in the Tontemboan language, which meet the criteria of polylexicality, sharpness, and idiomaticity. This has never been done in previous research.